2003
DOI: 10.1063/1.1564872
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated pre-oxidation method for healing progressive electrical short in organic light-emitting devices

Abstract: The accelerated pre-oxidation method (APOM) was applied to heal progressive electrical short (PES) in organic light-emitting devices. The APOM applied to the devices showed approximately 100 times lower leakage current and 25% improvement in device efficiency compared to a normal device without the APOM applied. The mean projected lifetime of the APOM devices was more than 2400 h at initial luminance of 100 cd/m2 and 90 °C, whereas the normal device turned off after 15 h of operation at the same temperature du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
43
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 17 publications
2
43
0
Order By: Relevance
“…Residual products from the polymer synthesis/deposition, chemical reactions among device elements as well as the presence of oxygen and water may promote internal device degradation, which is observed even when hermetic encapsulation is used. [11] Devices based on two other conjugated polymers, ITO/ PPV/Al [PPV: poly(p-phenylene vinylene)] and ITO/ PDOFV/Ca [PDOFV: poly(9,9 0 -dioctyl-2,7-fluorenylene vinylene], were also tested, presenting results which are qualitatively similar to those based on POT. …”
Section: Resultssupporting
confidence: 54%
“…Residual products from the polymer synthesis/deposition, chemical reactions among device elements as well as the presence of oxygen and water may promote internal device degradation, which is observed even when hermetic encapsulation is used. [11] Devices based on two other conjugated polymers, ITO/ PPV/Al [PPV: poly(p-phenylene vinylene)] and ITO/ PDOFV/Ca [PDOFV: poly(9,9 0 -dioctyl-2,7-fluorenylene vinylene], were also tested, presenting results which are qualitatively similar to those based on POT. …”
Section: Resultssupporting
confidence: 54%
“…In case of OLED displays made using small molecules, it has been reported that a progressive electrical short (PES) phenomenon is responsible for the degradation of display pixels during long time operation [8]. This report claimed that the PES phenomenon is closely related to the formation of unstable defects in organic layers which eventually leads to catastrophic degradation of whole layers in pixels.…”
Section: Introductionmentioning
confidence: 88%
“…Next, a 20 nm thick hole-transporting layer (HTL), N,, was deposited at 0.1 nm/s. Onto the HTL an emission layer (EML), which is a mix of tris(8-hydroxyquinolinato) aluminum (Alq 3 ) and 9-benzothiazol-2-yl-1,1,6,6-tetramethyl-2,3,5,6,7a,11a-hexahydro-1H,4H-11-oxa-3a-aza-benzo [de]anthracen-10-one (C545T), was deposited as reported previously [8]. Then additional Alq3 layer (20 nm thick) as an electron-transporting layer (ETL) was deposited on top of the EML, followed by depositing LiF (0.7 nm, 0.01 nm/s) as an electron-injecting layer (EIL) and Al cathode (120 nm, 0.5 nm/s) through a shadow mask (open width = 200 μm; open length = 44 mm).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…4 However, the commercialization of OLED is still awkward and very limited to a small size display because the device reliability (lifetime) lags behind the criteria of consumer electronics, even though it has been improved by device engineering such as accelerated pre-oxidation method (APOM). 5 This teaches us a concrete lesson that enhancing device reliability depends critically on the intrinsic property of organic semiconductor materials which includes chemical, physical, and thermal stabilities. In this regard, we have extensively studied thermally stable polymers and hybrid composite systems.…”
Section: Introductionmentioning
confidence: 99%